Digital transformation in firms: determinants of technology adoption and implications for performance - Silvia Massini; Mabel Sanchez Barrioluengo; Xiaoxiao Yu; Reza Salehnejad (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2024)
Advanced digital technologies (DTs) such as AI, Big Data, Cloud Computing, 3D printing, IoT, and Robotics are known for their potential to be pervasive and generate disruptive change. Despite this, there is limited evidence regarding the factors that motivate or hinder technology adoption. This study, based on an original survey of firms in Greater Manchester, aims to shed light on the determinants of DT adoption, including underlying motivations, potential barriers, and skills deficits. Additionally, it explores the influence of digitalisation and skills on firms` performance. Our results suggest that while different DTs are at varying stages of technology diffusion, they are characterised by complementarity and are often jointly adopted. Furthermore, the adoption of DTs in SMEs and younger firms, coupled with the presence of appropriate (digital and non-digital) skills, constitutes a pivotal synergy that significantly influences firms' productivity levels.
Keywords: 330; Digital transformation; Adoption; Skills; Motivations; Barriers; Productivity; Firms